What students who perform in "secondary roles" can learn from scenario training in vocational education - David Sjöberg; Staffan Karp; Oscar Rantatalo (International Journal for Research in Vocational Education and Training (IJRVET), 2019)
Context: Learning through scenario training and live simulation in vocational education is generally regarded as an effective tool for developing professional knowledge. However, previous research has largely overlooked the learning of students in secondary roles in scenario training. The objective of this study is to explore learning for students who act in secondary roles during scenario training in vocational educational settings. Method: The studied case entails scenario training for police students in a Swedish police education programme. A case study design, which included both participant observation and a questionnaire, was used. The analytic lens applied was inspired by practice theory and focused on how structural and situational arrangements of the training activity affect learning. Results: Our findings show that students who act in secondary roles learn from their scenario training experiences, but this learning often is overlooked in the design of training activities. Due to the structural arrangements of training activities, learning emerged as students in secondary roles were tasked to support the primary participants in relation to their learning objectives. In addition, it emerged in how students in secondary roles used previous scenario training experiences in relation to the current scenario and its learning objectives. Examples of learning from situational arrangements emerged as students in secondary roles formulated and provided feedback to primary participants and through informal discussions and reflection processes. Learning also emerged as students in secondary roles embodied the 'other' during scenario training, something that provided the students with new perspectives on police encounters. Conclusions: We theorize and extract three dimensions for how learning emerges in this case for secondary participants. It emerges through embodying the 'other', in students' sensory experiences, and through reconstruction of knowledge through repetition. However, our findings also show that learning for students in secondary roles can be improved through mindful set-up and design. Based on the findings, our article provides a discussion and suggestions on how scenario training can be planned and set-up to develop professional knowledge for students in secondary roles.
Keywords: 330; Scenario Training; Simulation; Vocational Education and Training; VET; Learning; Police Education; Practice